HECT E3 Ubiquitin Ligase-Regulated Txnip Degradation Facilitates TLR2-Mediated Inflammation During Group A Streptococcal Infection - Tseng, Po-Chun; Kuo, Chih-Feng; Cheng, Miao-Huei; Wan, Shu-Wen; Lin, Chiou-Feng; Chang, Chih-Peng; Lin, Yee-Shin; Wu, Jiunn-Jong; Huang, Chi-Chen; Chen, Chia-Ling (Frontiers in Immunology, 2019)
Thioredoxin-interacting protein (Txnip) inhibits the activity of thioredoxin (Trx) to modulate inflammatory responses. The burden of inflammation caused by microbial infection is strongly associated with disease severity; however, the role of Txnip in bacterial infection remains unclear. In Group A Streptococcus (GAS)-infected macrophages, Txnip was degraded independent of glucose consumption and streptococcal cysteine protease expression. Treatment with proteasome inhibitors reversed GAS-induced Txnip degradation. The activation of Toll-like receptor 2 (TLR2) initiated Txnip degradation, while no further Txnip degradation was observed in TLR2-deficient bone marrow-derived macrophages. NADPH oxidase-regulated NF-B activation and pro-inflammatory activation were induced and accompanied by Txnip degradation during GAS infection. Silencing Txnip prompted TLR2-mediated inducible nitric oxide synthase (iNOS)/NO, TNF-, and IL-6 production whereas the blockage of Txnip degradation by pharmacologically inhibiting the HECT E3 ubiquitin ligase with heclin and AMP-dependent protein kinase with dorsomorphin effectively reduced such effects. Our findings reveal that TLR2/NADPH oxidase-mediated Txnip proteasomal degradation facilitates pro-inflammatory cytokine production during GAS infection.